Desain Model Layanan Infrastruktur Berbasis Private Cloud Computing untuk Usaha Kecil Menengah - Imam Asrowardi; Eko Subyantoro (Jurnal Ilmiah ESAI, 2014)
The importance of the role of Small and Medium Enterprises for Indonesian economic growth appears to create a design cloud-based information technology infrastructure. The purpose of this research is the creation of an infrastructure design that can be used by small and medium enterprises to market their products through cloud computing services. The method used in this study is the system development life cycle(SDLC).Key words: cloud, technology, information, Small and Medium scale Enterprises